Perbandingan Algoritma N-gram dan Algoritma Knuth Morris Pratt untuk Mengukur Tingkat Akurasi Plagiarisme pada Dokumen Abstrak Skripsi Berbasis Website - Dwi Krisbiantoro; Sofyan Fathur Rohim; Irfan Santiko (Universitas Boyolali, 2021)
Plagiarism is a crime that often occurs in the academic world, plagiarism occurs because of theft of other people's work that is illegally recognized as if the work is his own. N-gram is an algorithm by cutting as many characters as N-characters in a sentence or word. While the Knuth Morris Pratt (KMP) algorithm is a string search algorithm, this algorithm is used to maintain information that is used to carry out the number of shifts whenever there is no matched patency in the text. The purpose of this study is to create a system to measure the comparison of the accuracy of the N-gram algorithm with a website-based KMP on a thesis abstract document. This research uses the waterfall system development method which has stages, namely analysis, design, coding, and testing. The KMP test results are better than N-gram where kmp has an average percentage of 3.8% while the N-gram 3.5% results are obtained from an average of 10 trials and 5 documents tested.